2020
DOI: 10.1016/j.neurobiolaging.2020.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis-associated DNA methylomic variation in Alzheimer's disease cortex

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…only epigenome-wide association study (EWAS) of psychosis in AD conducted to date identified two differentially methylated regions of the genome, located in TBX15 and WT1 which are both implicated in the pathophysiology of AD [124]. Interestingly the top-ranked differentially methylated positions were enriched in known schizophrenia-associated genetic and epigenetic variants, supporting a common mechanism of psychosis.…”
Section: Genomicsmentioning
confidence: 97%
“…only epigenome-wide association study (EWAS) of psychosis in AD conducted to date identified two differentially methylated regions of the genome, located in TBX15 and WT1 which are both implicated in the pathophysiology of AD [124]. Interestingly the top-ranked differentially methylated positions were enriched in known schizophrenia-associated genetic and epigenetic variants, supporting a common mechanism of psychosis.…”
Section: Genomicsmentioning
confidence: 97%
“…Study of the epigenome has led to major advances in the understanding of the molecular mechanisms underlying a variety of psychiatric and neurological conditions [71][72][73] . Hypomethylation in the TBX15 and WT1 genes, which have been implicated in the pathophysiology of AD, was found in the dorsolateral prefrontal cortex, superior temporal gyrus and entorhinal cortex in individuals with AD psychosis 74 . Interestingly, and reflecting some of the emerging data from genomic studies, the top-ranked differentially methylated regions also showed enrichment for known schizophrenia-associated genetic and epigenetic variants.…”
Section: Genomicsmentioning
confidence: 99%
“…Indeed, several studies have shown robust alterations in DNA methylation in a number of genes in different neurodegenerative diseases, in both the brain and blood, including Alzheimer's disease (AD) [23][24][25] , PD [26][27][28] and Dementia with Lewy bodies (DLB) 29 . Interestingly, associations have also been reported for secondary symptoms of these neurodegenerative disease, for example with psychosis symptoms in AD 30 or cognition in PD 27 . However the analysis of DNA methylation signatures in relation to PD secondary symptoms is understudied and has predominantly been undertaken in peripheral tissues such as blood 31 .…”
Section: Introductionmentioning
confidence: 94%